Emergency and Disaster Preparedness in Nurses: A Concept Analysis - SeyedehNegar Pourvakhshoori; Hamid Reza Khankeh; Farahnaz Mohammadi (Journal of Holistic Nursing and Midwifery)
Introduction: Given the growing rate of accidents and disasters in the world, preparing nurses as the main group responding to these events is crucial; however, a review of literature suggests no comprehensive and theoretical or practical definitions for this concept in nursing, which has been often misunderstood and used as an alternative to other similar concepts.